Resistance Induction in Olive Tree (Olea europaea) Against Verticillium Wilt by Two Beneficial Microorganisms and a Copper Phosphite Fertilizer - López-Moral, Ana; Llorens, Eugenio; Scalschi, Loredana; García-Agustín, Pilar; Trapero, Antonio; Agustí-Brisach, Carlos (Frontiers in Plant Science, 2022)
Enhancement of the plant’s natural defenses by beneficial microorganisms, i.e. endophytic bacteria and fungi or fertilizers such as copper phosphonates, could result in a potential alternative strategy against Verticillium Wilt of Olive tree (Olea europaea; VWO). In this study, two beneficial microorganisms (the fungus Aureobasidium pullulans AP08 and the bacterium Bacillus amyloliquefaciens PAB-024) and a phosphonate salt copper phosphite (CuPh) were evaluated for their effectiveness as host resistance inducers against Verticillium dahliae in olive. To this end, 6-month-old healthy olive plants of the susceptible cultivar Picual were treated by foliar or root applications by spraying 15 ml per plant or by irrigation with 350 ml per plant of the dilutions of each product (CuPh: 3 or 10 ml/l-1, respectively; PAB-024: 108 UFC ml-1; AP08: 106 UFC ml-1). Treatments were conducted weekly from two weeks before inoculation to 10 days after inoculation. A cornmeal-water-sand mixture (1:2:9; w:v:w) colonized by V. dahliae was used for plant inoculation. Additionally, treated and non-inoculated, non-treated and inoculated, and non-treated and non-inoculated plants were included for comparative purposes. Disease severity progress and shoot fresh weight were assessed. Parameters involved in plant resistance were monitored through determination and quantification of reactive oxygen species (ROS) response (H2O2), and evaluation of hormones by gene expression analysis. A. pullulans and CuPh were the most effective in disease reduction in planta by foliar or root application, respectively. Plants treated with CuPh showed significantly higher shoot fresh weight compared to the other treatments. ROS was significantly enhanced in plants treated with B. amyloliquefaciens PAB-024 compared to the rest of treatments and control. Concerning hormones evaluation, high levels of salicylic acid were detected on leaves from all treatment combinations, but without significant enhancements compared to the non-treated control. Regarding the gene expression related to salicylic acid, only the WRKY5 gene has shown a strong enhancement in the treatment with B. amyloliquefaciens. On the other hand, a strong accumulation of jasmonic acid and jasmonic acid-isoleucine in plants treated with A. pullulans was observed in all the tissues analyzed as well as in roots of plants treated with B. amyloliquefaciens and CuPh.